The Longitudinal Effects of Violence Exposure on Delinquency and Academic Outcomes for African-American Youth - Cooper, Adina (2017)
There are millions of violent crimes reported each year in communities across the United States, disproportionately affecting ethnic minority and low-income communities. Violence exposure has harmful effects on residents and significant implications for adolescent development. Youth who are exposed to violence are at greater risk for problem behaviors and experiences, including delinquency and low academic performance (Baskin & Sommers, 2014; Patton, Wooley, & Hong, 2012). Many of the consequences of violence exposure impact trajectories of adolescent development and can be observed well into adulthood. However, some youth overcome the challenges associated with violence exposure and successfully transition into adulthood. Resilience theory and the protective factors model provide a lens to examine how positive social environmental influences may lessen the impact of contextual risk factors and promote desirable outcomes for youth exposed to violence (Fergus & Zimmerman, 2005; LÃ¶sel & Farrington, 2012). In this study, I used structural equation modeling (SEM) to examine the role of perceptions of neighborhood connectedness and school belonging as protective factors for the effects of violence exposure on delinquency, criminal involvement, academic behavioral engagement and educational attainment over time, for a sample of African-American youth. It was hypothesized that connectedness to oneâ€™s neighborhood and sense of belonging to school would moderate the mediational associations among violence exposure, adolescent adjustment measures (i.e., delinquency and academic behavioral engagement) and adult outcomes, demonstrating a protective effect for the influence of violence exposure on developmental outcomes for youth. The findings indicated that the model was a good fit for the data. More violence exposure significantly predicted more delinquency; violence exposure did not predict academic behavioral engagement, however. More delinquency predicted lower academic behavioral engagement, and school belonging predicted less delinquency. The mediational hypotheses were not supported, and the results showed that neighborhood connectedness and school belonging did not have protective effects for the influence of violence exposure on the adolescent adjustment variables. Instead, neighborhood connectedness significantly predicted more delinquency and did not significantly predict academic behavioral engagement. The results highlight important considerations about neighborhood effects on youth risk behaviors and developmental outcomes. This study contributes to the literature on ecological risk and protective factors for adolescent delinquency and academic engagement. The findings can inform the development of community and school-based interventions to promote positive development for African-American adolescents exposed to violence